ANALISIS CORPORATE SOSIAL RESNONSIBILITY TERHADAP KINERJA KEUANGAN - Nurcahyaningsih, Indah; Rachman, Arif Nugroho (JAB (Jurnal Akuntansi & Bisnis), 2018)
The purpose of the study is to analyze the effect of corporate social responsibility (CSR) on financialperpormance. Study sample of manufacturing companies in the cosmetics and household goods sector. Data analysis using multiple liniar regression, t test, F test, and R2 test. The results of the study have the effect of economic perpormance on return on equity (ROE) in manufacturing companies in the cosmetics and household goods sector. There is influence on the perpormance of labor practices and decent work on ROE in manufacturing companies in the cosmetics and household goods sector. There is an influence of human rights perpormance on ROE in manufacturing companies in the cosmetics and household goods sector. There is an influence of social perpormance on ROE in manufacturing companies in the cosmetics and household goods sector. There is no effect on product responsibility perpormance on ROE in manufacturing companies in the cosmetics and household goods sector.Â Keywords: CSR, financial Performance, ROE